Influence of the Multiplicity Yerba Mate Brewing on the Antioxidant Activity of the Beverages - Dmowski, P.; Post, L. (Scientific Journal of Gdynia Maritime University, 2018)
Infusions prepared from yerba mate are good sources of antioxidants, especially polyphenols, that are very important to its healthy and sensory properties. The presence of these compounds largely depends on the method and multiplicity of brewing. The aim of this work is to evaluate the influence of the multiplicity of brewing on the antioxidant activity of yerba mate beverages prepared from Ilex paraguariensis. It was found that each subsequent yerba mate brewing reduces the antioxidant properties of beverages. It was found that each subsequent yerba mate brewing statistically important reduces the total content of polyphenols. The change in total polyphenols content was reduced even by approximately 85%.